Serum antioxidant enzymes and malondialdehyde levels in patients with premature ejaculation before and after pharmacotherapy - Atmaca, M; Karadag, F; Tezcan, E (Oxford Univ Press, 2005)
Background. In our previous study, significantly higher antioxidant enzymes and malondialdehyde (MDA) levels in patients with premature ejaculation (PE) compared to healthy controls were found. In the present study, we planned to evaluate antioxidant enzymes and MDA levels of patients with PE before and after citalopram treatment. Methods. The study comprised 30 patients with PE according to Diagnostic and Statistical Manual of Mental Disorders Fourth Version (DSM-IV) and 30 healthy controls. The patients were randomly assigned to two groups. Fifteen of them (group I) received 8 weeks of citalopram treatment but the remaining (group II) did not. The subjects were asked to determine the average intravaginal ejaculation latency time (IVELT). The fasting antioxidant enzymes and MDA levels were measured at baseline and after 8 weeks. Results. No statistically significant difference in the mean WELT between groups at baseline was found. WELT considerably elevated after 8 weeks of citalopram treatment in group I with a mean of 209 +/- 72.1 seconds but not in group II. Antioxidant enzymes and MDA levels did not differ between groups at baseline. At the evaluation of week 8, SOD, GSH-Px, and NIDA levels significantly reduced during treatment in group I patients. Conclusion. In conclusion, the results suggest that the ability for antioxidant enzymes and MDA to normalize through symptom alleviation reveals that they might be trait market of PE. Further placebo-con trolled studies are needed.
Keywords: SOD; CAT; GSH-Px; MDA; premature ejaculation; citalopram